2016
DOI: 10.14235/bs.2016.704
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Antioxidants are Double-edged Swords

Abstract: Oxidant-antioxidant balance is crucially important in maintaining healthy biological systems. Under physiological conditions, the human antioxidative defense system, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and glutathione (GSH), allows the elimination of excess reactive oxygen species (ROS), including superoxide anions (O 2 . ), hydroxyl radicals (HO .), and alkoxyl radicals (RO .). In addition, exogenous compounds with reducing capacity, such as vitamin C, vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The stimulation of bioactive compounds accumulation in P. caerulea leaves, especially of polyphenols and flavonoids, could lead to combinations with reduced safety [83]. High doses of polyphenols proved to be toxic in some cases [84]; therefore, a screening of the safety of treated plant extracts was considered to be necessary. An in vitro method based on cultured cell viability assay was selected for safety screening of the blue passion flower extracts.…”
Section: Cytocompatibility Of the Extracts From The Treated Leavesmentioning
confidence: 99%
“…The stimulation of bioactive compounds accumulation in P. caerulea leaves, especially of polyphenols and flavonoids, could lead to combinations with reduced safety [83]. High doses of polyphenols proved to be toxic in some cases [84]; therefore, a screening of the safety of treated plant extracts was considered to be necessary. An in vitro method based on cultured cell viability assay was selected for safety screening of the blue passion flower extracts.…”
Section: Cytocompatibility Of the Extracts From The Treated Leavesmentioning
confidence: 99%
“…This condition worsens due to the presence of several divalent metal ions such as Fe, Cu, and other transition metal ions which will reduce antioxidant activity. Antioxidants provide the most reductive power in the presence of the fenton reaction along with increased OH formations (Koçyiğit & Selek, 2016). This reaction has the potential to increase the detrimental effects from free radical activities.…”
Section: Discussionmentioning
confidence: 99%
“…While antioxidants reduce oxidative stress at low doses, they have therapeutic doses that can increase the selective death of cancer cells and the effectiveness of standard treatment by increasing ROS production with a prooxidative effect at high doses (65). Studies have been shown that RSV at different concentrations offers favorable suppression of cancer generation and cancer treatment as RSV mediates cytotoxicity in cancer cells by increasing intracellular hydrogen peroxide (H 2 O 2 ) and oxidative stress levels that will cause cell death (66).…”
Section: Inhibiting Cancer Formation By Regulating Oxidative and Geno...mentioning
confidence: 99%